Perakitan dan Pengembangan Varietas Unggul Sorgum untuk Pangan, Pakan, dan Bioenergi - Herman Subagio; Muh Aqil (Puslitbang Tanaman Pangan, 2014)
Sorghum crop has a potential to support the food-energy program in Indonesia.Sorghum contains high carbohydrate, antioxidants, minerals, protein and fiber. As a source of bioenergy, sorghum has the potential for substituting fossil fuel. High demand for sorghum in the international market gives an opportunity for Indonesia to produce the grain more, for domestic and export markets. To date, thirteen sorghum varieties had been released, each with specific characteristics, such as high-yielding, early maturing and wide adaptability. Sweet sorghum varieties (i.e. Super-1 and Super-2) are designated for producing ethanol to develop bioindustry in Indonesia. Optimizing the sorghum production is needed to provide material for the upstream and downstream industries. To avoid the landuse competition among crop commodities, sorghum production should be expanded to the marginal lands and the non-productive lands in central and eastern part of Indonesia. Strong government support is needed to establish the seed production subsystem, followed by seed procurement for the crop expansion program. To improve the germplasm background on the varietal development, local strains as genetic resources should be explored to be used on the development of sorghum varieties for specific environment.